Ideological Shift in Indian Higher Education Internationalization - Kahre, Mona (International Higher Education, 2014)
A new strategy sees India seeking to become a regional education hub by developing new forms of international collaboration based on co-creation, opening up to private education provision for dual and joint degrees, and entering international associations for knowledge sharing. But, it will need to ensure that appropriate strategies and quality assurance systems are in place at the different levels to ensure successful outcomes.